2022
DOI: 10.1186/s12943-022-01668-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in brain tumors: current therapeutic significance and future prospects

Abstract: Brain cancer is regarded among the deadliest forms of cancer worldwide. The distinct tumor microenvironment and inherent characteristics of brain tumor cells virtually render them resistant to the majority of conventional and advanced therapies. Oxidative stress (OS) is a key disruptor of normal brain homeostasis and is involved in carcinogenesis of different forms of brain cancers. Thus, antioxidants may inhibit tumorigenesis by preventing OS induced by various oncogenic factors. Antioxidants are hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 273 publications
(379 reference statements)
0
20
0
1
Order By: Relevance
“…The latter was accompanied by a decrease in the concentration of MDA in the blood and tumors, which also confirmed the antioxidant protective effect of the extract. From the published literature, antioxidant protection leads to anti‐inflammatory, antiproliferative, antimetastatic, and antiangiogenic effects 95 . The above‐mentioned processes were studied by evaluating the changes in the activity of arginase, the quantity of polyamines, NO, and IL‐2, and breast histological analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was accompanied by a decrease in the concentration of MDA in the blood and tumors, which also confirmed the antioxidant protective effect of the extract. From the published literature, antioxidant protection leads to anti‐inflammatory, antiproliferative, antimetastatic, and antiangiogenic effects 95 . The above‐mentioned processes were studied by evaluating the changes in the activity of arginase, the quantity of polyamines, NO, and IL‐2, and breast histological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…From the published literature, antioxidant protection leads to antiinflammatory, antiproliferative, antimetastatic, and antiangiogenic effects. 95 The above-mentioned processes were studied by evaluat- The activity of arginase and NOS enzymes may be accompanied by an increase in the activity of COX-2, which is a key process in inflammation. 97 Further studies will be needed to determine the role of HA in immune responses in the settings of breast cancer.…”
Section: Ha Exhibits High Antioxidant Activity In An In Vivo Modelmentioning
confidence: 99%
“…It is known that plants commonly produce antioxidants, however, the degree of antioxidant activity may be higher when species-specific metabolites with specialised antioxidant activity are present (Zonyane et al, 2020 ). The antioxidant activity of natural antioxidant substances is uncertain and condition dependent, therefore it is important to perform both in vitro and in vivo analysis before making claims with regards to potentially therapeutic antioxidant substances (Gupta et al, 2020 ; Qi et al, 2022 ). In this particular study, an in vitro assay was thus conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The classical therapeutic scheme of brain cancer includes surgical resection followed by chemotherapy and/or radiation therapy. However, a growing body of evidence revealed that the chances of relapse are very high for malignant brain tumors [ 8 , 9 ].…”
Section: Brain Tumors: Clinical Constraints Towards Treatmentmentioning
confidence: 99%